The gender gap in intergenerational mobility: Evidence of educational persistence in Brazil - Tharcisio Leone (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2017)
This paper employs mobility matrices, univariate regressions and multivariate econometric techniques based on the recently published nationally representative household survey (PNAD-2014) from Brazil to investigate the relevance of the gendered patterns in the intergenerational transmission of educational attainment between parents and their descendants. The empirical evidence from these three different approaches is absolutely unanimous: In Brazil there is a significant variation in degree of mobility across genders, with a higher mobility level for daughters than for sons. The reason for this gender gap in mobility lies in the chances of attaining the educational levels: regardless of the educational background of the parents, females have a lower chance of remaining without school certificate and a greater probability to achieve a tertiary education. The results of this paper point out also that the educational attainment of children is strongly associated with the education of their most educated parent, regardless of their gender and this correlation is higher for female than for male. Concerning the evolution of the persistence in education over time, the findings indicate for both sexes a significant increase in intergeneration mobility over the last decades. However this positive evolution is much more modest when the relative deviation in education across generations is excluded from the investigation. Finally, this study has demonstrated that parental occupation levels and individual characteristics (race, locality of residence and year of birth) also have a statistically significant effect on the prospects for mobility.
Keywords: J62; I21; J16; 330; Intergenerational Mobility; Educational Persistence; Gender Gap; Brazil